Genetic analysis of the 3′ untranslated region of the bovine SLC11A1 gene reveals novel polymorphisms - Hasenauer, Flavia Carolina; Caffaro, María Eugenia; Czibener, Cecilia; Comerci, Diego José; Poli, Mario Andres; Rossetti, Carlos Alberto (Springer, 2019)
Polymorphisms in microsatellites at the 3′ untranslated region (3′UTR) of the SLC11A1 (solute carrier family 11 member A1) gene have been associated with natural resistance to Brucella abortus and Mycobacterium bovis infection in livestock species. Here, we carried out an individual genetic analysis of the two microsatellites present at the 3′UTR SLC11A1 gene in 254 Bos taurus purebred, 125 B. indicus purebred and 54 B. taurus × B. indicus crossbred cattle. The genotyping by capillary electrophoresis showed the presence of four alleles (157, 159, 161 and 163) for the first microsatellite (MS1) and six alleles (175, 177, 179, 181, 183 and 185) for the second microsatellite (MS2). The alleles 159 and 175 were the most frequent in all breeds analyzed. B. taurus showed the most homogeneous haplotype and genotype for both microsatellites, whereas B. indicus showed the most heterogeneous haplotype and genotype. Two novel variants (alleles 161 and 163) within the MS1 are reported as well as novel variants in MS2 in Holstein breed. The knowledge of the polymorphisms distribution in both microsatellites at the 3′UTR of the SLC11A1 gene in cattle breeds is useful for future experimental design to evaluate the association between reported genotypes and natural resistance to pathogens infection.